Beispiel Nr: 10
$ \text{Gegeben:}\\\text{Umfang} \qquad U \qquad [m] \\ \text{Länge} \qquad a \qquad [m] \\ \\ \text{Gesucht:} \\\text{Breite} \qquad b \qquad [m] \\ \\ b = \frac{U - 2\cdot a}{ 2}\\ \textbf{Gegeben:} \\ U=160m \qquad a=13m \qquad \\ \\ \textbf{Rechnung:} \\ b = \frac{U - 2\cdot a}{ 2} \\ U=160m\\ a=13m\\ b = \frac{160m - 2\cdot 13m}{ 2}\\\\b=67m \\\\\\ \tiny \begin{array}{|l|} \hline a=\\ \hline 13 m \\ \hline 130 dm \\ \hline 1,3\cdot 10^{3} cm \\ \hline 1,3\cdot 10^{4} mm \\ \hline 1,3\cdot 10^{7} \mu m \\ \hline 0,013 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline U=\\ \hline 160 m \\ \hline 1,6\cdot 10^{3} dm \\ \hline 1,6\cdot 10^{4} cm \\ \hline 1,6\cdot 10^{5} mm \\ \hline 1,6\cdot 10^{8} \mu m \\ \hline 0,16 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline b=\\ \hline 67 m \\ \hline 670 dm \\ \hline 6,7\cdot 10^{3} cm \\ \hline 6,7\cdot 10^{4} mm \\ \hline 6,7\cdot 10^{7} \mu m \\ \hline 0,067 km \\ \hline \end{array}$